PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PT. INALUM - Nabila Audria; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
This study aims to determine the level of work stress (X) and employee performance (Y) at MotherAnd Baby Magazine, and whether there is a significant influence between work stress on employee performance at PT. Inalum. Sampling used the saturated sample method, namely by directly selecting all 35 employees. While the method of data collection method used is to use a Questionnaire (Survey) to all employees of PT. Inalum. The methods used to process and analyze the data are Product Moment Correlation Test, Correlation Test, and Significance Coefficient Correlation Test (t test). Based on the results of the study, it showed that there was a very strong or positive significant influence between work stress on employee performance as indicated by a correlation coefficient of 0.880 and a coefficient of determination of 77.44%. This means that work stress affects performance by 77.44%, the remaining 22.56% is influenced by other factors. After the significance test was carried out, the result was 10.643, then Ho was rejected and Ha was accepted, meaning that there is a significant influence between work stress on employee performance